Leaves as dining plates, food wraps and food packing material: Importance of renewable resources in Indian culture - Kora, Aruna Jyothi (2021)
In India, serving food on leaf dining plates is a long-standing tradition with its own cultural, religious, medicinal, and socioeconomic significance. The leaf plate stitching is a livelihood activity for tribal people in Odisha, Madhya Pradesh, Chhattisgarh, Andhra Pradesh, and Telangana states of India. The leaves and leaf plates are used for offering naivedyam to god during worship and distribution of prasadam to devotees. They are extensively used for serving food during marriages, religious festivals, community feasts, etc. The leaves from a vast variety of plants are used as dining plates, food wraps during steam cooking, grilling and frying of various dishes, and food packing material in India.